PENERAPAN IPTEKS TENTANG PENTINGNYA PROTOKOL KESEHATAN DAN STRATEGI PEMERINTAH UNTUK MENGHADAPI COVID-19 VARIAN OMICRON DI KELURAHAN KOYA BARAT - James Yoseph Palenewen; Daniel Tanati; Elias Hence Thesia; Marthinus Solossa (AMMA : Jurnal Pengabdian Masyarakat, 2023)
This service was carried out with the title Application of Science and Technology Regarding the Importance of Health Protocols and Government Strategies for Dealing with the Omicron Variant Covid-19 which was carried out in the West Koya Village, Muara Tami District, Jayapura City, activities carried out for partners due to cases from partners that there were still many people who did not comply what health protocols and strategies should the government use to reduce the rate of increase in positive numbers from the Covid-19 Variant Omicron which is currently rife in Jayapura City so that with the expertise possessed by servants, they can implement the science and technology. The method of implementing this community service is by implementing science and technology through lectures and discussions which will be held on Thursday, June 2, 2022, at the Koya Barat Village Office and providing assistance to partners that has been carried out to date. This activity begins with preparation and coordination with partners in providing knowledge about the importance of the 5M health protocol and the strategies used by the government to reduce the positive rate of the Covid-19 Variant Omicron in Jayapura City. The output of this service is to provide partners with an understanding of the importance of health protocols and strategies used by the government to suppress the positive rate of Covid-19 Variant Omicron in Jayapura City.